KEMAMPUAN KETERAMPILAN MEMBACA ANAK DENGAN TINGKAT KEPARAHAN DISLEKSIA BERAT SISWA SMP MAKASSAR MULYA (STUDI KASUS) - Nurul Ramadhani Mukhtar; Ramly; Usman (Journal Studies in Indonesian Language and Literature, 2024)
The purpose of this study was conducted to describe the ability of reading skills of dyslexiwc students at Makassar Mulya Junior High School. The results showed that dyslexic students at Makassar Mulya Junior High School are included in the severe dyslexia level because students have difficulty in understanding all forms of words, especially words containing similar letters, students have very little focus in following the learning process, students cannot interact well, students' brain work is very slow, and seen from the age of students who have entered 16 years. This happens because of the slow awareness of parents so that the handling of students is slow. Therefore, the student has reached the severity of the severe category. Severe dyslexia must certainly be handled specifically in the learning process and get full support around it.